HLA-B46 is associated with severe sacroiliitis in Japanese patients with psoriatic arthritis. Issue 6 (2nd November 2019) - Ikumi, Kyoko; Kobayashi, Shigeto; Tamura, Naoto; Tada, Kurisu; Inoue, Hisashi; Osaga, Satoshi; Nishida, Emi; Morita, Akimichi
Abstract: Objectives: The aim of the present study was to determine if the HLA phenotype is related to severe sacroiliitis in Japanese patients with psoriatic arthritis. Methods: This study was a single-center, retrospective, cross-sectional, observational study. We reviewed the clinical information and radiologic examinations of patients with psoriatic arthritis (PsA) who visited our hospital from January 2011 to December 2016. Radiographic changes in the sacroiliac joints were assessed by four independent investigators according to the recommendations of the Assessment of Spondyloarthritis International Society. Results: Of 113 PsA patients, 63 (55.8%) had sacroiliitis. The HLA phenotype was investigated in 39 patients. Ordered logistic regression analysis revealed that the presence of HLA-B46 was an independent risk factor for severe sacroiliitis in Japanese PsA patients (odds ratio 3.2; 95% confidence interval 1.16–9.81). Therefore, the clinical features were divided into two groups according to the presence of HLA-B46. Both the Nail Psoriasis Severity Index and grade of sacroiliitis were significantly higher in the HLA-B46–positive group (Mann-Whitney U test; p  = .0003 and p  = .028, respectively). Conclusion: HLA-B46 is considered a risk factor for severe sacroiliitis in Japanese patients with PsA.